2015
DOI: 10.1039/c5ra10625g
|View full text |Cite
|
Sign up to set email alerts
|

Quantum chemical and experimental insights for the ionic liquid facilitated thermal dehydrogenation of ethylene diamine bisborane

Abstract: The current work reports the judicial selection and subsequent dehydrogenation reaction with ionic liquid (IL) facilitated ethylene diamine bisborane (EDAB). Quantum chemical based COSMO-SAC (COnductor like Screening MOdel Segment Activity Coefficient) model was initially used to screen the ILs as available from Sigma Aldrich. LUMO-HOMO calculation was then performed to analyze the stability of EDAB/IL complexes. The molecular modeling studies converged on the two ILs, namely 1-ethyl-3-methyl imidazolium aceta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 33 publications
1
25
1
Order By: Relevance
“…Palladium and ruthenium nanoparticle‐supported hydrophobic IL‐based scaffolds were used for this work. Banerjee et al employed QC‐based screening to screen acetate‐based ILs from a pool of 205 ILs. In a subsequent report, Banerjee et al employed reactive force field simulation to elucidate the EDAB/IL desorption mechanism.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Palladium and ruthenium nanoparticle‐supported hydrophobic IL‐based scaffolds were used for this work. Banerjee et al employed QC‐based screening to screen acetate‐based ILs from a pool of 205 ILs. In a subsequent report, Banerjee et al employed reactive force field simulation to elucidate the EDAB/IL desorption mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…The dehydrogenation reaction was then performed at 105°C. The reason for selection of this temperature is due to the fact that approximate release of 4 equivalent of hydrogen was obtained from EDAB/IL system at 105°C . Further, Himmelberger et al reported an absence of induction period for dehydrogenation of AB/IL system at 105°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is evident that imidazolium IL facilitates a faster and higher amount of hydrogen release, in line with the similar trend for IL-assisted dehydrogenation of EDAB. 16,18 Upon heating, the TBAB/[BMIM][OAc] system instantly releases hydrogen. A single equivalent of hydrogen is seen to release within 30 min of dehydrogenation, and after 180 min, the release becomes negligible.…”
Section: Resultsmentioning
confidence: 99%
“…Sahler et al 15 also reported the use of imidazolium IL, which lowers the activation energy and enhances the yield of hydrogen for the dehydrogenation of ethylene diamine bisborane (EDAB). Banerjee et al 16 recently reported a 3.96 equiv yield of H 2 at 105 °C from EDAB using 1-butyl-3-methylimidazolium acetate ([BMIM]-[OAc]) IL. In combination with basic anions, imidazolium cations exert a strong effect on the yield of hydrogen.…”
Section: Introductionmentioning
confidence: 99%